Duration and Sitting Habits with The Prevention of Scoliosis - Loustha, Amanda Cahaya; Nur Fajri, Dinda; Indrawati, Lina (Poltekkes Kemenkes Semarang, 2025)
Background: Scoliosis is a spinal disorder influenced by factors, including sitting duration and habits, Adolencents with poor sitting habits and long sitting duration are at higher risk of developing scoliosis. Purpose: This study analyzes the relationship between duration and habits with the preventation of scoliosis in adolescent at Madrasah Aliyah 02 Babelan Bekasi and determine the most dominan variable in the preventation of scoliosis. Methods: This quantitative study employed an observational analytic design. With 130 respondents through Simple Random Sampling. Data collection used questionnaires covering duration, sitting habits, and scoliosis prevention. Analysis utilized the Krusskal-Wallis test to examine relationships between variables and logistic regression to determine the dominant factor influencing scoliosis preventation (α = 0.05). Results: Kruskal-Wallis testing revealed significant relationships between sitting habits and scoliosis preventation (p=0.001). Logistic regression showed only duration significantly affected scoliosis preventation (p=0.006), while sitting habits were not significant (p=0.125). Conclusion: Duration is the dominant factor affecting scoliosis preventation in adolescents, while sitting habits showed no significant effect in the regression model. Increasing awereness about safe duration limits and promoting physical activity are necessary to reduce scoliosis risk.